North African Migration under Surveillance. Between Home Country an Host Country - (:unkn) unknown (My University, 2014)
The spectacular nature of the migration crisis in 2011 can undoubtedly be seen as a singular and exceptional episode. It was in fact an important, though somewhat spasmodic, element in the migration policy followed over the last twenty years between Europe and North Africa.To support this hypothesis, this article will review the issues involved in readmission agreements between EU Member States and North African countries as a way of controlling migration, after a discussion of dual migratory flows that are on the increase: illegal departures towards Europe and the arrival of a Sub-Saharan population in North Africa since the 1990s. In addition, it will attempt to analyse the reinforcement of migratory controls in North Africa which were set up in 2003 when the EU decided to fix its external borders through the integration of new members. In addition to participating in the policy for cooperation over border controls and humanitarian aid, North African countries were now part of a wider – Mediterranean-wide – process as they found themselves becoming countries of destination and transit for populations from the South. Today, as work begins on drafting new constitutions, some of these countries, such as Tunisia, are reflecting on the terms of new national legislation on the rights of refugees.
Keywords: African Research